Root Words and Derived Words in Indonesian Language Textbooks for Grades 1 and 2: Morphological Study - Hanun Zahronida; Abdul Kholiq (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the use of root words and derived words in Indonesian language textbooks for grades 1 and 2 of elementary school and to compare them based on morphological analysis. The method used is quantitative with a descriptive-comparative approach. Data collection techniques were carried out through documentation techniques using the "listen, read, engage, and note-taking" technique for textbooks at both levels. Data analysis was carried out in two stages: descriptive analysis to describe the distribution of vocabulary based on word classes, number of occurrences, and morphological processes; and comparative analysis to compare the distribution of vocabulary between levels based on the number of entry names. The results show that the number of vocabulary items in the grade 1 elementary school textbooks reaches 6,357, while the grade 2 elementary school textbooks are 8,217. Based on the entry name analysis, the grade 1 elementary school textbook contains 858 words, consisting of 540 root words and 318 derived words. Meanwhile, the grade 2 elementary school textbook contains 1,353 words, consisting of 850 root words and 503 derived words. Comparisons between grades reveal differences in word count and variety, particularly in the use of root words and derived words, which are more prevalent in second-grade textbooks. This indicates an increase in linguistic complexity with increasing grade level. The study concludes that root words are more dominant than derived words in both first and second grades. This dominance of root words reflects the adaptation of language materials to the developmental stages of elementary school students' language skills at each grade.